Assessing the role of Parental Behavior and Peer Pressure in the Development of Juveniles Delinquent Behavior among Higher Secondary School Children’s: In Punjab, Pakistan (An Empirical Framework) - Ashraf, Muhammad Umair; Ahmad, Abd Halim; Talib, Azlizan (Bahauddin Zakariya University, Multan, Pakistan, 2020)
This article presents empirical and theoretical underpinning between parental behavior, peer pressure and juvenile delinquent behavior among higher secondary school children in Punjab, Pakistan. A total of 815 male and females' students were involved in this study with a response rate of 770. The data collection was conducted form six districts of Punjab (Lahore, Kasur, Okara, Sahiwal, Khanewal and Lodhran) by using a multistage sampling technique. However, the validation of adapted scales has been examined by second-order confirmatory factor analysis, and hypotheses were tested by using the structural equation modelling technique (SEM). The findings of this study revealed that parental behavior has significant negative association with juvenile delinquent behavior (β = -0.447; t = 14.602, P <0.000), while peer pressure has significant positive association with juvenile delinquent behavior (β = 0.413, t = 16.043, P <0.000). This study concluded that peer pressure is the highest influential factor increasing juvenile delinquent behavior, whereas parental behavior negatively influencing juvenile delinquent behavior. Moreover, findings are discussed in relation to refining present taxonomic arguments about delinquency and practical implications for the prevention of juvenile delinquent behavior